Prequantization of the Moduli Space of Flat PU(p)-Bundles with Prescribed Boundary Holonomies - Krepski, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
Using the framework of quasi-Hamiltonian actions, we compute the obstruction to prequantization for the moduli space of flat PU(p)-bundles over a compact orientable surface with prescribed holonomies around boundary components, where p>2 is prime.